1988
DOI: 10.1042/bj2540211
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-, calcium- and concentration-dependence of acetylcholine stimulation of insulin release and ionic fluxes in mouse islets

Abstract: Mouse islets were used to define the glucose-dependence and extracellular Ca2+ requirement of muscarinic stimulation of pancreatic beta-cells. In the presence of a stimulatory concentration of glucose (10 mM) and of Ca2+, acetylcholine (0.1-100 microM) accelerated 3H efflux from islets preloaded with myo-[3H]inositol. It also stimulated 45Ca2+ influx and efflux, 86Rb+ efflux and insulin release. In the absence of Ca2+, only 10-100 microM-acetylcholine mobilized enough intracellular Ca2+ to trigger an early but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
3

Year Published

1988
1988
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 41 publications
5
50
0
3
Order By: Relevance
“…Several, but not necessarily all effects brought about by ACh in B-cells are interconnected [17,18]. Slight differences in the potencies of the antagonists on ACh-induced insulin release and on 86Rb+ or 45Ca2+ efflux were noted.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several, but not necessarily all effects brought about by ACh in B-cells are interconnected [17,18]. Slight differences in the potencies of the antagonists on ACh-induced insulin release and on 86Rb+ or 45Ca2+ efflux were noted.…”
Section: Discussionmentioning
confidence: 98%
“…This peak is due to Ca2+ mobilization (peak of 45Ca2+) by inositol trisphosphate. However, concentrationdependence studies have shown that the relationship between insulin release and the magnitude of Ca2+ mobilization is non-linear [18]. A small decrease in mobilization, as that produced by the lowest concentration of antagonists, is sufficient to cause a marked reduction in release.…”
Section: Discussionmentioning
confidence: 99%
“…Glybenclamide, a sulfonylurea drug, induces membrane depolarization and insulin secretion by directly blocking the SUR1/Kir6.2 K ATP channel (35). Carbachol, a cholinergic agonist, enhances GSIS via the phospholipase C/protein kinase C signaling pathway and is suggested to increase the transport of insulin vesicles to the secretory site (1,36,37). These secretagogues depend, at least partly, on intact glucose metabolism for their ability to stimulate insulin secretion (36 -42).…”
Section: Resultsmentioning
confidence: 99%
“…1) was completely suppressed by coincubation with 50 µmol/l of the L-type Ca 2+ -channel blocker verapamil, a well known inhibitor of glucoseinduced insulin release [33,34]. On the contrary, acetylcholine (Table 1), a neurotransmitter that mobilizes calcium ions from intracellular stores in beta cells [35] did not influence cAMP content in beta cells. However, potentiating effects of acetylcholine on insulin release from purified cells were observed (p<0.005; Table 1).…”
Section: Receptor-mediated Camp Accumulation In Beta Cellsmentioning
confidence: 97%